(untitled) (Revista Electrónica Calidad en la Educación Superior, 2024)
The purpose of this writing is to share some actions, strategies and technological resources used in the implementation of the self-evaluation process with a view to the accreditation of the Bachelor’s degree in Pedagogy with an emphasis in Didactics (LPED), of the Division of Educology (DE); as well as offering different alternatives to develop self-assessment processes under a remote presence modality in emerging contexts due to the health emergency. The self-assessment report of the LPED culminated in 2020, an atypical year marked by the COVID-19 pandemic.